Population PK and PK/PD modelling of microencapsulated octreotide acetate in healthy subjects - Zhou, Honghui (Blackwell Science Inc, 2000)
AIMS: To develop a population model that can describe the pharmacokinetic profile of microencapsulated octreotide acetate in healthy cholecystectomized subjects. To investigate the correlation between serum IGF-1 and octreotide concentration. METHODS: A population pharmacokinetic analysis was performed on octreotide data obtained following a single dose of 30 mg microencapsulated octreotide acetate intramuscularly. The relationship between serum IGF-1 concentration and octreotide concentration was effectively described by a population pharmacokinetic/pharmaco-dynamic model. RESULTS: The pharmacokinetic profile of octreotide was characterized by an initial peak of octreotide followed by a sustained-release of drug. Plateau concentration were sustained up to day 70, and gradually declined to below the detection limit by day 112. A one-compartment linear model was constructed which consisted of two absorption processes, characterized by K(IR) and K(SR), rate constants for immediate-release and sustained-release, respectively, with first-order elimination (K(e); 1.05 h(−1)). The surface, unencapsulated drug was immediately absorbed into the central compartment with first-order absorption (K(IR) 0.0312 h(−1)), while the microencapsulated drug was first released in a zero-order fashion into a depot before being absorbed into the central compartment with first-order absorption (K(SR); 0.00469 h(−1)) during a period of τ (1680 h). Body weight and gender were important covariates for the apparent volume of distribution. The type of formulation was an important covariate for K(IR) but had no effect on K(SR). An inhibitory E(max) population pharmacokinetic/pharmacodynamic model could adequately describe the relationship between IGF-1 (expressed as percent baseline) and octreotide concentration. Baseline IGF-1 concentration was found to be a significant covariate for the baseline effect (E(0)). A relationship between GH concentration and octreotide concentration was not established. CONCLUSIONS: The pharmacokinetic profile of microencapsulated octreotide acetate was effectively described by the derived population model. The relationship between IGF-1 and drug concentration could be used to guide optimization of therapeutic octreotide dosage regimens.